'I didn't know why you had to wait': an evaluation of NHS infant‐feeding workshops amongst women living in areas of high deprivation. Issue 6 (11th September 2014) - Andrews, E. J.; Symon, A.; Anderson, A. S.
Abstract: Background: Inappropriate maternal and infant‐feeding practices are known to have a major impact on morbidity in infancy, childhood and later life. Ring‐fenced funding over 3 years from the Scottish Government to the National Health Service (NHS) in Scotland has allowed the development of a range of nutrition interventions for women of childbearing age and infants living in areas of deprivation to help address these issues. The present study aimed to determine mothers' knowledge of appropriate infant‐feeding practices, opinions about feeding advice and any changes in practice following attendance at workshops. Methods: Fifteen semi‐structured interviews with women who participated in NHS infant‐feeding workshops. Verbatim transcripts were analysed using framework analysis. Results: Participants appreciated the opportunity to enhance their knowledge and there was evidence of a reasonable understanding and awareness of appropriate infant‐feeding behaviours following workshop attendance. However, the findings highlight the challenge of multiple sources of advice and identify persistent uncertainties about feeding practice. Reported feeding behaviour following workshops was encouraging (e.g. delayed weaning, increased use of ‐prepared fruits and vegetables), although there was also evidence of resistance to change. The legacy of the workshop in terms of reported confidence in infant feeding was also apparent. Conclusions: The workshops appears to aid current knowledge and practice about infant feeding but further work is needed to examine the long term impact of these interventions on maternal and infant dietary behaviours.